Multiplicity of Mathematical Modeling Strategies to Search for Molecular and Cellular Insights into Bacteria Lung Infection - Cantone, Martina; Santos, Guido; Wentker, Pia; Lai, Xin; Vera, Julio (Frontiers in Physiology, 2017)
Even today two bacterial lung infections, namely pneumonia and tuberculosis, are among the ten most frequent causes of death worldwide. These infections still lack effective treatments in many developing countries and in immunocompromised populations like infants, elderly people and transplanted patients. The interaction between bacteria and the host is a complex system of interlinked intercellular and the intracellular processes, enriched in regulatory structures like positive and negative feedback loops. Severe pathological condition can emerge when the immune system of the host fails to neutralize the infection. This failure can result in systemic spreading of pathogens or overwhelming immune response followed by a systemic inflammatory response. Mathematical modelling is a promising tool to dissect the complexity underlying pathogenesis of bacterial lung infection at the molecular, cellular and tissue levels, but also at the interfaces among levels. In this article, we introduce mathematical and computational modelling frameworks that can be used for investigating molecular and cellular mechanisms underlying bacterial lung infection. Further, we compile and discuss published results on the modelling of regulatory pathways and cell populations relevant for lung infection and inflammation. Finally, we discuss how to make use of this multiplicity of modeling approaches to open new avenues in the search of the molecular and cellular mechanisms underlying bacterial infection in the lung.